Clinical and Radiological Outcome of Titanium Implants in Clinical Practice: A 5 Year, Prospective, Multicenter Case Series - Claude Jaquiéry; Bernd Ilgenstein; Markus Jungo; Konrad Rüeger; Stephan Chenaux; Adam Papadimitropoulos; Kurt Jäger (MDPI AG, 2014)
The objective of this prospective clinical case series was to confirm the 5-year clinical and radiographic performance of titanium implants occlusally loaded after 12 weeks. Periapical X-rays for quantitative bone level assessment were taken immediately post-surgery, after loading, 6 and 12 months, and 5 years after loading. Pocket depth (PD) and clinical attachment level (CAL) were measured. One-hundred and fourteen implants were inserted in 71 consecutive patients; 111 (97%) implants/69 (97%) patients were followed for 5 years. One implant was lost before loading (acute infection of unknown origin). Another patient developed peri-implantitis in the healing phase, and underwent successful surgical revision. Mesial median bone level at 6 and 12 months, and 5 years was 1.2 (SD ± 0.7), 1.3 (SD ± 0.7) and 1.1 (SD ± 0.6) mm; distal values were: 1.1 (SD ± 0.7), 1.4 (SD ± 0.7) and 1.2 (SD ± 0.6) mm; below implant shoulder. Stable CAL (1.2-1.6 mm) and PD (2.0-3.0 mm) were found. After 5 years no implant was lost. Three crowns and one abutment screw were defective and replaced. Implant survival (1 failure/114) as well as minimal peri-implant bone loss confirmed the favorable outcome of the used implant line. Five years post-loading, crestal bone stabilized slightly below the machined/rough border.